The complement system and age-related macular degeneration. - Sivaprasad, S; Chong, N (2006)
PURPOSE: Age-related macular degeneration (AMD) is the leading cause of blindness in the developed world. There are increasing evidences to suggest the complement system may play a significant role on the pathogenesis of AMD. In this review, we summarise the current research in this area. METHODS: Review of literature. RESULTS: The complement system is a complex system with several activation pathways. Complement factor H (CFH) polymorphisms has been associated with increase risk of AMD. CFH is an inhibitor protein; the polymorphisms might cause uncontrolled activation by initiation events. CONCLUSION: Further studies on the molecular basis of the complement-mediated pathogenesis of AMD may offer novel therapy to AMD.